Impact of COVID‐19 on the mental health in a cohort of Italian rehabilitation healthcare workers. Issue 1 (23rd August 2021) - Farì, Giacomo; de Sire, Alessandro; Giorgio, Vincenzo; Rizzo, Laura; Bruni, Antonella; Bianchi, Francesco P.; Zonno, Alessandra; Pierucci, Paola; Ranieri, Maurizio; Megna, Marisa
Highlights: Depressive, anxiety, and burnout were present in Italian healthcare workers during COVID‐19 pandemic. A depersonalization factor showed to be significant increased. The 47.1% of the operators reported a depressive state. The female gender conferred greater risks for depression. Abstract: The COVID‐19 pandemic has had a strong impact on healthcare workers (HCWs), affecting their physical and mental health. In Italy, HCWs have been among the first exposed to unprecedented pressure, dealing with large numbers of infections during the first pandemic wave. However, the severe psychological consequences on HCWs find little evidence in the literature, especially in terms of comparison to the status quo ante pandemic. The aim of this study was to provide an assessment of the mental health burden in a cohort of Italian HCWs during the COVID‐19 pandemic, comparing their condition with that before the emergency, to direct the promotion of mental well‐being among HCWs worldwide. In this retrospective study, we included physicians, physical therapists, and nurses working in the Respiratory Intensive Care Unit, Neurology Unit, and Rehabilitation Unit from a Southern Italy University Hospital. All study participants underwent a battery of psychological tests, aimed at verifying their state of mental health during the COVID‐19 emergency and before it. Depressive, anxiety, and burnout symptoms were assessed using the following questionnaires: Maslach Burnout Inventory, Patient Health Questionnaire‐9 (PHQ‐9), and General Anxiety Disorder‐7. Depressive, anxiety, and burnout clinical relevance symptoms were present in HCWs during the COVID‐19 pandemic more than those before the emergency. Fifty percent of the HCWs obtained a score clinically significant during the emergency. Moreover, a depersonalization factor showed a statistically significant increase in average scores ( p  < 0.0001). The PHQ‐9 scale showed that 47.1% of the operators reported depressive state presence. The number of operators scoring above the cut‐off for the anxiety scale tripled during the emergency ( p  < 0.0001). The female gender conferred greater risks for depression. Taken together, the findings of this study showed that our sample of Italian HCWs showed a greater risk for depression, anxiety, and stress during the COVID‐19 pandemic. These data might be a starting point to plan mental health monitoring and prevention programs for HCWs, thus ensuring patients receive the best possible care performances even during healthcare crises such as the current pandemic.